Analisis Strategi Pemasaran Syariah Telur Ayam Ras Studi Kasus Peternakan Berkah Abadi Desa Opo-opo - Lutfir Rahman, Alif; Aziz, Abd; Ghafur, Abd (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2023)
This study aims to analyze the distribution method, determine the weaknesses and deficiencies as well as the opportunities and threats in the sale of purebred chicken eggs used at the Berkah Abadi farm in Opo-opo Village. Based on the results of the study, the steps used in the marketing method of broiler eggs at Berkah Abadi Farm in Opo-opo Village are by using three sales patterns, namely the first. from breeders to wholesalers (poultry shop) after that it is distributed to middle traders, after that it goes to retailers, then it is distributed to consumers. The second pattern is from breeders, distributed to middle traders, after that retail traders, then distributed to consumers. And the third method is from breeders distributed to retail traders and then directly distributed to consumers. Another appropriate pattern that can be used in selling purebred chicken eggs is by using internal strength, in this way it can prevent external threats so that it will not have an excessively negative impact on egg marketing. Then by maintaining the quality of the eggs so that they remain quality eggs by keeping the chickens from getting sick and later this will also help make the farm sustainable. Keywords: strategy, Marketing, Chicken Egg Race